IMPACT OF WOMEN'S RELIGIOUS MARRIAGE RIGHTS ON THEIR SOCIO-ECONOMIC PERSPECTIVE - Anjum, Shabana (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Religious marriage rights play a significant role in shaping the socio-economic status of women in different societies. These rights affect access to education, employment, property ownership and economic independence. This research paper explores the relationship between religious marriage rights and socio-economic status, analysing how different religious doctrines and legal frameworks affect the empowerment or marginalisation of women. In addition, it presents studies from different regions to highlight the inequalities that exist and progress made in ensuring equal rights. The study concludes that while religious marriage rights can provide women with social security and identity, they also often reinforce patriarchal structures, which can limit women's socio-economic progress.